2009
DOI: 10.1007/s10548-009-0125-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Transcranial Magnetic Stimulation on Spike Pattern and Topography in Patients with Focal Epilepsy

Abstract: Repetitive Transcranial Magnetic Stimulation (rTMS) is a non-invasive method for brain stimulation. Group-studies applying rTMS in epilepsy patients aiming to decrease epileptic spike- or seizure-frequency have led to inconsistent results. Here we studied whether therapeutic trains of rTMS have detectable effects on individual spike pattern and/or frequency in patients suffering from focal epilepsy. Five patients with focal epilepsy underwent one session of rTMS online with EEG using a 6 Hz prime/1 Hz rTMS pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Several studies have shown that after low frequency rTMS treatment in epileptic patients the number of interictal spikes on EEG decreases significantly (Brodbeck et al, 2010;Fregni et al, 2005;Joo et al, 2007;Menkes and Gruenthal, 2000;Santiago-Rodriguez et al, 2008) and this effect lasts approximately for two months (Misawa et al, 2005). The anticonvulsive action of rTMS has also been shown in laboratory animals (Akamatsu et al, 2001;Mongabadi et al, 2013;Tokay et al, 2009;Yadollahpour et al, 2014); however, a few studies have been done to determine the effect of rTMS on neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that after low frequency rTMS treatment in epileptic patients the number of interictal spikes on EEG decreases significantly (Brodbeck et al, 2010;Fregni et al, 2005;Joo et al, 2007;Menkes and Gruenthal, 2000;Santiago-Rodriguez et al, 2008) and this effect lasts approximately for two months (Misawa et al, 2005). The anticonvulsive action of rTMS has also been shown in laboratory animals (Akamatsu et al, 2001;Mongabadi et al, 2013;Tokay et al, 2009;Yadollahpour et al, 2014); however, a few studies have been done to determine the effect of rTMS on neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, testing this type of hypothesis is particularly challenging using conventional neuroimaging or behavioral techniques, due to the difficulty of distinguishing between excitatory or inhibitory processes. In order to overcome this limitation transcranial magnetic stimulation (TMS) – a non-invasive technique allowing the excitation or inhibition of specific brain regions through magnetic pulses – has been largely used to study the properties of given cortico-spinal pathways (Miniussi and Thut, 2010) both in healthy and clinical populations (Brodbeck et al, 2010; Rotenberg, 2010). The features of the “motor-evoked potentials” (time-locked electromyographic activity resulting from a supra-threshold TMS pulse over the motor cortex) and cortical silent period (CSP; the interval of silent electromyographic activity following a supra-threshold TMS pulse) can provide information regarding the underlying state of the neural populations.…”
Section: Potential Mechanisms Of Fhdmentioning
confidence: 99%
“…Yet, results from placebo-controlled trials are mixed, with one trial demonstrating a reduction in seizures and improvement of (off-line) EEG [107], and two others showing insignificant clinical improvement, or improvement of the EEG without a significant reduction in seizures [108][109][110]. Finally, Brodbeck et al [111] found no decrease in seizure frequency after rTMS [111]. Among the factors contributing to the inconsistent findings in antiepileptic rTMS trials may be the difficulty in selecting an appropriate intensity of extramotor TMS, i.e., stimulation output intensity outside the motor cortex.…”
Section: Tms In Epilepsy: a Rationale For Neuromodulationmentioning
confidence: 99%